A polymer brush modified molecular imprint photoelectrochemical sensor and its preparation method and application
By introducing polymer brushes on the electrode surface of the photoelectrochemical sensor, blocking the nonspecific adsorption sites of dopamine polymers, the problem of degradation of traditional photoelectrochemical sensors in protein detection is solved, achieving higher specificity and sensitivity.
Patent Information
- Application Number
- CN202211650412.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-21
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-12-21
AI Technical Summary
In protein detection, traditional photoelectrochemical sensors have reduced recognition ability due to poor environmental stability of biological macromolecules, and the rich active functional groups on the surface of dopamine polymers lead to nonspecific adsorption, which reduces the qualitative analysis ability.
Through surface-induced atom transfer radical polymerization, polymer brushes are introduced on the imprinted PDA of the electrode, blocking the functional groups at the non-imprinted sites and reducing non-specific adsorption of proteins, thereby improving the qualitative analysis capability of the MIP-PEC sensor.
It effectively blocks the non-specific adsorption sites on the PDA surface, improves the sensor's specific recognition ability and quantitative analysis accuracy of proteins, and significantly improves the detection sensitivity.
Smart Images

Figure CN115931998B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photoelectrochemical sensors, and in particular relates to a polymer brush modified molecular imprinting photoelectrochemical sensor and a preparation method and application thereof. Background Art
[0002] Proteins are basic elements of all organisms and play an important role in physiological processes. It is of great significance to conduct qualitative and quantitative analysis on them. Many methods have been tried for protein detection, including spectrophotometry, fluorescence spectroscopy, mass spectrometry, enzyme-linked immunosorbent assay, electrochemical method, etc. As a branch of electrochemical methods, photoelectrochemical (PEC) sensing has the advantages of high detection sensitivity, simple operation, and easy miniaturization. In addition, as the excitation source of PEC sensing, light can achieve the separation of input and output signals, which greatly improves the sensitivity of protein detection.
[0003] In order to achieve effective recognition of different proteins by photoelectrodes, the traditional method is to modify the photoelectrodes with biomacromolecules such as antibodies and DNA chains that have good selective pairing with proteins. However, due to the poor environmental stability of biomacromolecules, their application in PEC detection of proteins is limited. In order to replace biomacromolecules, researchers introduced molecular imprinting polymers (MIPs) into the field of PEC detection of proteins. The combination of MIP and PEC technology (MIP-PEC) has the advantages of strong specific recognition, good stability, and easy design and synthesis. In the field of protein detection of MIP-PEC, MIP-PEC can be divided into MIP-PEC based on inorganic monomers and MIP-PEC based on organic monomers.
[0004] MIP-PEC based on inorganic monomers. SiO2 is the most common inorganic monomer, and proteins are used as template molecules. On the surface of the photoelectrode, the organosilicon source is hydrolyzed in the presence of protein molecules to produce SiO2, completing the molecular imprinting process. Since SiO2 has good hydrophilicity, nonspecific adsorption of proteins can be avoided. In addition, the thickness of SiO2 on the electrode increases linearly with the extension of the hydrolysis time of the organosilicon source, which makes the thickness of the MIP layer easy to control. However, the presence of a large amount of organic solvents during the synthesis of SiO2 leads to conformational changes in the protein template, thereby reducing the recognition ability of the MIP-PEC sensor during the detection process.
[0005] MIP-PEC based on organic monomers. Organic molecules and proteins serve as functional monomers and template molecules, respectively. On the surface of the photoelectrode, organic molecules are polymerized in the presence of protein molecules to complete the molecular imprinting process. During the polymerization of organic molecules, protein denaturation needs to be avoided, so mild polymerization conditions are essential. Organic ionic liquid polymerization and dopamine polymerization are well known for their mild conditions and have recently been used as functional monomers for MIP-PEC for protein sensing. Polyionic liquids have the advantages of good solubility, high conductivity, adjustable structure, and multiple interaction sites with template molecules.
[0006] In addition, previous work has found that ionic liquids can protect protein structures and can be polymerized at low temperatures, which is suitable for MIP-PEC detection, such as ionic liquids BCPEimBr and PMIMBr. However, most ionic liquids are gel-like after polymerization, and the imprinting sites are easily deformed, resulting in poor stability. Polydopamine (PDA), a polymerization product of dopamine, exhibits good imprinting stability, high biocompatibility, and strong adhesion to the electrode surface. Therefore, dopamine is a suitable functional monomer that ensures the conformational stability of the protein template and the stability of the imprinting site. It has been applied to PEC detection of bovine hemoglobin and human hemoglobin.
[0007] However, the abundant active functional groups on the PDA surface can lead to the adsorption of analytes and interferents at non-imprinted sites, which will deteriorate the detection ability of MIP-PEC. How to overcome this problem is worth considering. Summary of the invention
[0008] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0009] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0010] One of the objectives of the present invention is to provide a molecular imprinting photoelectrochemical sensor, which introduces a polymer brush on the imprinted PDA of the electrode through surface-initiated atom transfer radical polymerization, blocks the functional groups at non-imprinting sites, reduces the nonspecific adsorption of PDA to proteins, and thus improves the qualitative analysis capability of the MIP-PEC sensor.
[0011] In order to solve the above technical problems, the present invention provides the following technical solutions: a molecular imprinting photoelectrochemical sensor, comprising:
[0012] an electrode substrate, comprising a semiconductor material capable of generating electrons and holes under illumination;
[0013] A molecular imprinting layer is attached to the surface of the electrode substrate, wherein the molecular imprinting layer has a plurality of template sites, each template site being specific to a particular molecule or biomacromolecule; and
[0014] a polymer brush, the polymer brush occupying a non-template site portion of the molecular imprinting layer;
[0015] Wherein, the material of the polymer brush is selected from one of PEGMA and its derivatives.
[0016] As a preferred embodiment of the polymer brush modified molecular imprinting photoelectrochemical sensor of the present invention, the material of the molecular imprinting layer is selected from one or more of polydopamine, polyacrylamide and its derivatives, polyacrylic acid and its derivatives, chitosan, gelatin, polyvinyl alcohol, polymethacrylic acid, silicon dioxide, and titanium dioxide.
[0017] As a preferred embodiment of the polymer brush modified molecular imprint photoelectrochemical sensor of the present invention, the template site is specific to one or more of bovine serum albumin, insulin, bovine hemoglobin, horse myoglobin, human growth hormone, ribonuclease, glucose oxidase, catalase, and raw material compounds prohibited by cosmetics.
[0018] Among them, the "prohibited raw material compounds for cosmetics" refer to harmful substances that cannot be added to cosmetics as raw materials for the production of cosmetics. The "Technical Specifications for Safety of Cosmetics" (2015 edition) stipulates the requirements for prohibited and restricted components of cosmetics, forming the "Catalogue of Prohibited Raw Materials for Cosmetics", which includes 1-(1-naphthylmethyl)quinolinium, acetylcholine and its salts, 2-bromopropane, 3,3'-dichlorobenzidine, 4-tert-butylphenol, 6-amino-o-cresol and its salts, 7-methylcoumarin, acrylonitrile, allolamide and its salts, aminocaproic acid and its salts, amitriptyline and its salts, apomorphine and its salts, azacycline and its salts, benztropine and its salts, benzylparaben, benzo[a]pyrene, benzo[k]fluoranthene, urotropine, benzoyl peroxide, cannabidiol and other compounds.
[0019] As a preferred embodiment of the molecular imprinting photoelectrochemical sensor modified by the polymer brush of the present invention, wherein:
[0020] The electrode substrate comprises a silicon substrate, a carbon layer or a doped carbon layer attached to the silicon substrate, and a semiconductor material layer attached to the carbon layer or the doped carbon layer;
[0021] Wherein, the silicon substrate has a micro-pyramid structure surface.
[0022] Among them, the semiconductor material is a semiconductor material that can generate electrons and holes under light, including but not limited to Cu2O, ZnO, PbO, Co3O4, Fe2O3, BiVO4, TiO2, WO3, Ta2O5, GaN, InP, CdS, CdSe, SiC, Si, Ge and other semiconductor materials.
[0023] Another object of the present invention is to provide a method for preparing a molecular imprinting photoelectrochemical sensor modified with a polymer brush as described in any one of the above, comprising:
[0024] providing an electrode substrate;
[0025] A molecular imprinting layer is formed by polymerizing a molecular imprinting layer monomer containing a template material on the surface of an electrode substrate;
[0026] The eluted template material forms a plurality of template sites on the molecular imprinting layer and a functional group capable of initiating atom transfer radical polymerization is formed on the non-template site portion;
[0027] The polymer brushes are formed by functional group-mediated atom transfer radical polymerization of the polymer precursor at the non-template site.
[0028] As a preferred solution of the preparation method of the polymer brush modified molecular imprinting photoelectrochemical sensor of the present invention, wherein: the molecular imprinting layer monomer containing the template material is polymerized on the surface of the electrode substrate, the electrode substrate is placed in a PBS solution containing the molecular imprinting layer monomer and the template material, and the polymerization is stirred to obtain an electrode substrate with a molecular imprinting layer.
[0029] As a specific embodiment of the present invention, the material of the molecular imprinting layer is polydopamine (PDA), the monomer of the molecular imprinting layer is dopamine (DA), and the template material is bovine serum albumin (BSA). At this time, the electrode substrate is immersed in a DA concentration of 0.5 to 50 mg mL -1 PBS solution (pH = 8.5) for 1 hour to pre-deposit PDA; then the above sample was placed in a solution containing functional monomer dopamine (0.5-50 mg / mL -1 ) and template BSA (0.1-10 mg mL -1 ) in a PBS solution (pH=8.5) and stirred for polymerization at a polymerization time of 30 to 600 min and a polymerization temperature of 10 to 60° C. to obtain an electrode substrate with a molecular imprinting layer.
[0030] As a preferred embodiment of the preparation method of the polymer brush modified molecular imprinting photoelectrochemical sensor of the present invention, the template material is eluted, and the electrode substrate having the molecular imprinting layer is immersed in a mixture of dichloromethane and triethylamine. Under a N2 atmosphere, a dichloromethane solution containing 2-bromoisobutyryl bromide is added dropwise to the above solution, and then stirred at room temperature. Thereafter, the template material is eluted with acetic acid / sodium dodecyl sulfate to form an electrode substrate having a molecular imprinting layer with template sites and functional groups.
[0031] As a specific embodiment of the present invention, the material of the molecular imprinting layer is polydopamine (PDA), the monomer of the molecular imprinting layer is dopamine (DA), and the template material is bovine serum albumin (BSA). When eluting the template material, the electrode substrate with the molecular imprinting layer is immersed in a mixture of 80 mL DCM and 0.8 mL TEA, and 20 mL DCM solution containing 2% BiBB is added dropwise to the above solution at 0° C. for 1 hour under N2 atmosphere, and then stirred at room temperature for 12 hours to obtain Br-MIP / TiO2 / CN / Si P ; The BSA template was then eluted with acetic acid / SDS (10% v / v: 5% w / v) for 30 to 120 min to form an electrode substrate with a molecular imprinting layer having template sites and functional groups.
[0032] As a preferred scheme of the preparation method of the polymer brush modified molecular imprinting photoelectrochemical sensor of the present invention, wherein: the functional group-mediated atom transfer radical polymerization of the polymerization precursor occurs at the non-template site portion, the polymerization precursor solution is deoxygenated by N2 bubbling, an electrode substrate having a molecular imprinting layer with template sites and functional groups is contacted with the polymerization precursor solution, and polymerization is carried out at room temperature to obtain a polymer brush modified molecular imprinting photoelectrochemical sensor.
[0033] As a specific embodiment of the present invention, the material of the molecular imprinting layer is polydopamine (PDA), the monomer of the molecular imprinting layer is dopamine (DA), the template material is bovine serum albumin (BSA), the material of the polymer brush is poly (ethylene glycol) methacrylate (PEGMA), the polymerization precursor solution is composed of PEGMA, 2,2-bipyridine, methanol and H2O, the molecular weight of PEGMA is 100 to 1000, the concentration of PEGMA is 50 to 2300 mg / mL, and the concentration of 2,2-bipyridine is 0.1 to 8.7 mg / mL When atom transfer radical polymerization occurs, the copper sheet is activated for 30 seconds with an equal volume of a mixed solution of 1M hydrochloric acid and methanol, and then fixed with a hollow rubber mold with a binder clip. Subsequently, the polymerization precursor solution is deoxygenated by N2 bubbling for 30 minutes and added to the hollow part of the rubber mold. The electrode substrate of the molecular imprinting layer with template sites and functional groups is covered on the top of the rubber mold to ensure contact with the polymerization precursor solution. Polymerization is carried out at room temperature for 0.5 to 5 hours at a polymerization temperature of 5 to 60°C to obtain a polymer brush modified molecular imprinting photoelectrochemical sensor.
[0034] As a preferred embodiment of the method for preparing the polymer brush modified molecular imprinting photoelectrochemical sensor of the present invention, the electrode substrate is provided by the following method:
[0035] The silicon wafer is etched in an alkaline solution with a hydroxide concentration of 10 -6 ~2mol / L, forming a silicon wafer with a micro-pyramid structure surface;
[0036] Putting the silicon wafer into a polymer monomer solution for polymerization, and polymerizing to form a polymer layer on the surface of the silicon wafer;
[0037] calcining the polymer layer to carbonize the polymer layer and form a carbon layer or a doped carbon layer on the silicon wafer;
[0038] The semiconductor material is assembled on the carbon layer or the doped carbon layer, and the electrode substrate is obtained after calcination.
[0039] As a specific embodiment of the present invention, the electrode substrate is provided by a specific method comprising: placing a silicon wafer in a KOH solution (the concentration of hydroxide is 10 -6 ~2mol / L) for 1 to 60 min at an etching temperature of 50 to 95° C. to form a silicon wafer with a micro-pyramid structure surface;
[0040] Spin-coat a 1-10 wt% ammonium dihydrogen phosphate solution on the Si substrate at a speed of 500-8000 rpm. P The silicon wafer is heated for 60 seconds and calcined at 350-1000°C for 0.5-10 hours, and the calcined silicon wafer is immersed in 5% HF to remove the phosphosilicate glass formed on the surface;
[0041] The sample is placed in a mixed aqueous solution of 10-100 mg / mL dopamine and 1-40 mg / mL tris(hydroxymethyl)aminomethane for polymerization, the polymerization reaction time is 10-300 min, the polymerization temperature is 10-60° C., and a polydopamine layer is formed on the surface of the silicon wafer;
[0042] Under the protection of N2, the silicon wafer with the polydopamine layer is calcined at 350-800°C for 0.5-10 hours to carbonize the PDA layer and form a nitrogen-doped carbon layer on the silicon wafer;
[0043] Spin-coat the titanium dioxide sol on the nitrogen-doped carbon layer. The concentration of the TiO2 sol is 10 -3 ~1mol / L, spin coating speed 500~8000rpm, and then calcined at 300~800℃ for 0.5~24h to obtain an electrode substrate.
[0044] Another object of the present invention is to provide a use of the polymer brush modified molecular imprinting photoelectrochemical sensor as described in any one of the above items in the detection of biomolecules and / or cosmetics.
[0045] Compared with the prior art, the present invention has the following beneficial effects:
[0046] The present invention introduces a polymer brush on the imprinted PDA of the electrode through surface-initiated atom transfer radical polymerization, blocks the functional groups at non-imprinted sites, reduces the nonspecific adsorption of PDA to proteins, and thus improves the qualitative analysis capability of the MIP-PEC sensor. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0048] Figure 1 The performance test comparison diagram of the electrode substrate obtained by Example 1 of the present invention and Comparative Examples 1 and 2; wherein (a) is TiO2 / CN / Si under chopping light irradiation P 、TiO2 / Si P and Si P Photoelectrode chronoamperometry; (b) TiO2 / CN / Si P 、TiO2 / Si P and Si P Nyquist plot of the photoelectrode (the inset is the equivalent circuit used for fitting); (c) TiO2 / CN / Si under chopped light P and TiO2 / CN / SiF Photoelectrode chronoamperometry; (d) TiO2 / CN / Si P and TiO2 / CN / Si F Reflectance spectrum of the photoelectrode.
[0049] Figure 2 The TiO2 / CN / Si in Examples 2 and 3 of the present invention P Chronoamperometry of photoelectrodes under chopped light illumination; wherein (a) is Example 2, and (b) is Example 3.
[0050] Figure 3 Preparation of rMIP(PB) / TiO2 / CN / Si P Schematic diagram of the process.
[0051] Figure 4 The SEM images of the materials prepared in Example 1 and Example 4 of the present invention; wherein (a) is a Si with a buried pn junction P SEM image of (b) CN / Si P SEM image of TiO2 / CN / Si P (d) is the SEM image of TiO2, (e) is the XRD pattern of MIP / TiO2 / CN / Si P SEM image of NIP / TiO2 / CN / Si P SEM images of (g) rMIP(PB) / TiO2 / CN / Si P (h) is the SEM image of PDA, MIP, Br-MIP and MIP(PB).
[0052] Figure 5 The rMIP(PB) / TiO2 / CN / Si prepared in Example 4 of the present invention P SEM and corresponding elemental mapping images.
[0053] Figure 6 The photocurrent density changes before and after BSA is eluted under different MIP conditions in Examples 5 to 7 of the present invention; wherein, (a) is Example 5 at different imprinting times, (b) is Example 6 at different BSA concentrations, and (c) is Example 7 at different elution times.
[0054] Figure 7 rMIP(PB) / TiO2 / CN / Si under different conditions in Examples 8 to 9 of the present invention P The photocurrent density of rMIP(PB) / TiO2 / CN / Si at different polymerization times in Example 8 PThe photocurrent density of (b) is the photocurrent density of rMIP(PB) / TiO2 / CN / Si in Example 9 P Changes in photocurrent density before and after different incubation times of BSA.
[0055] Figure 8 The photocurrent density and linear analysis of different concentrations of BSA solution in Example 9 of the present invention; wherein (a) is the photocurrent density of rMIP (PB) / TiO2 / CN / Si at different BSA concentrations P Chronoamperometry; (b) rMIP(PB) / TiO2 / CN / Si P Linear analysis between the photocurrent density change and the logarithm of BSA concentration.
[0056] Fig. 9 NIP / TiO2 / CN / Si with different BSA concentrations in the present invention P 、rMIP / TiO2 / CN / Si P 、rMIP(PB) / TiO2 / CN / Si P ΔI; where (a) is rMIP(PB) / TiO2 / CN / Si P With NIP / TiO2 / CN / Si P Comparison of (b) and (c) for rMIP / TiO2 / CN / Si P With NIP / TiO2 / CN / Si P comparison.
[0057] Fig.10 are the interferents and the selectivity under the interferents in Example 10 of the present invention; wherein (a) is the three-dimensional structure and structural formula of different interferents, and (b) is rMIP(PB) / TiO2 / CN / Si P and rMIP / TiO2 / CN / Si P Sensor selectivity towards different interferents.
[0058] Fig.11 The rMIP(PB) / TiO2 / CN / Si in Example 11 of the present invention P Stability test results of the photoelectrode; (a) shows five independent rMIP(PB) / TiO2 / CN / Si P (a) The repeatability of the photocurrent density of the electrode; (b) The stability of the photocurrent density during the photoswitching cycle within 400 seconds.
[0059] Fig.12 The detection results of acetylcholine in Example 13 of the present invention; wherein (a) is rMIP(PB) / TiO2 / CN / Si at different Ach concentrations P-Ach chronoamperometry; (b) rMIP(PB) / TiO2 / CN / Si P -Linear analysis between the photocurrent density change of Ach and the logarithm of Ach concentration; (c) is the structural formula of different interferents, (d) is rMIP(PB) / TiO2 / CN / Si P -Ach and rMIP / TiO2 / CN / Si P -Ach sensor selectivity for different interferents; (e) Five independent rMIP (PB) / TiO2 / CN / Si P -Repeatability of the photocurrent density of the Ach electrode; (f) stability of the photocurrent density during the photo-switching cycle within 400 seconds. DETAILED DESCRIPTION
[0060] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0061] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0062] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0063] Unless otherwise specified, the raw materials used in the examples were purchased commercially.
[0064] The photoelectrochemical measurement method used in the embodiment of the present invention is as follows:
[0065] Fabrication of the photocathode. First, a shallow groove was carved on the back of the electrode and a layer of gallium-indium alloy was coated on the groove. Second, a copper wire was placed on the surface of the alloy and glued with conductive silver glue to provide ohmic contact between copper and silicon. Finally, to insulate and protect the back contact of the silicon substrate, epoxy was applied to the entire sample except for the area where the front side was illuminated.
[0066] The detailed calculation process of the effective area of the electrode is as follows. ImageJ is a Java-based public image processing software developed by the National Institutes of Health. First, an optical photograph containing the electrode and the ruler is captured with a digital camera. Then, the optical photograph of the electrode with the ruler is imported into the ImageJ software. Subsequently, the ratio of the pixel size to the actual size is determined based on the ruler in the image. Finally, the area of the electrode surface not covered by epoxy resin is selected by the selection tool to calculate the actual area of the electrode.
[0067] Example 1
[0068] (1) A silicon wafer (2 cm × 2 cm) was etched in a KOH solution (1 M) at 85°C for 30 minutes to form a micro-pyramid-shaped silicon (Si P );
[0069] (2) Spin coat 5 wt% NH4H2PO4 solution on Si at 4000 rpm. P 60 seconds and calcined at 950°C for 1 hour. P Immerse in 5% HF to remove the phosphosilicate glass formed on its surface;
[0070] (3) The above sample was placed in a mixed solution of 1.48 g dopamine, 0.12 g Tris and 30 ml H2O at 30°C for 100 min. P PDA is formed on the surface, and then PDA / Si is formed. P ;
[0071] (4) PDA / Si was calcined at 500°C under the protection of N2. P 2 hours to carbonize the PDA layer. P Nitrogen-doped carbon (CN) is formed on the surface to obtain CN / Si P ;
[0072] (5) Spin-coat TiO2 sol on CN / Si P The TiO2 / CN / Si ... P .
[0073] Comparative Example 1
[0074] (1) A silicon wafer (2 cm × 2 cm) was etched in a KOH solution (1 M) at 85°C for 30 minutes to form a micro-pyramid-shaped silicon (Si P );
[0075] (2) Spin coat 5 wt% NH4H2PO4 solution on Si at 4000 rpm. P60 seconds and calcined at 950°C for 1 hour. P Immerse in 5% HF to remove the phosphosilicate glass formed on its surface;
[0076] (3) Spin-coat TiO2 sol on Si P The TiO2 / SiO2 was prepared by spinning at 4000 rpm for 30 s for 4 times and then calcined at 450 °C for 2 h to form TiO2 / Si P .
[0077] Comparative Example 2
[0078] (1) Prepare a 2 cm × 2 cm silicon wafer;
[0079] (2) A 5 wt% NH4H2PO4 solution was spin-coated on a silicon wafer at 4000 rpm for 60 seconds and calcined at 950°C for 1 hour. F Immerse in 5% HF to remove the phosphosilicate glass formed on its surface;
[0080] (3) The above sample was placed in a mixed solution of 1.48 g dopamine, 0.12 g Tris and 30 ml H2O at 30°C for 100 min. F PDA is formed on the surface, and then PDA / Si is formed. F ;
[0081] (4) PDA / Si was calcined at 500°C under the protection of N2. F 2 hours to carbonize the PDA layer. F Nitrogen-doped carbon (CN) is formed on the surface to obtain CN / Si F ;
[0082] (5) Spin-coat TiO2 sol on CN / Si F The TiO2 / CN / Si ... F .
[0083] Compared with Si P 、TiO2 / Si P and TiO2 / CN / Si P The chopped photocurrent and electrochemical impedance spectroscopy, such as Figure 1 As shown in a. P Compared with TiO2 / Si P The photocurrent density is higher. This is because the interface heterojunction is formed between TiO2 and Si, which improves the separation efficiency of photogenerated carriers, thereby significantly increasing the intensity of the photoelectric signal. In addition, it can be found that TiO2 / CN / Si PThe photocurrent density is significantly higher than that of TiO2 / Si P On the one hand, CN can improve the interface compatibility between Si and TiO2. On the other hand, CN itself is a conductive material. Therefore, CN can reduce the charge transfer resistance of carriers from Si to TiO2, thereby increasing the amplitude of signal enhancement.
[0084] Through electrochemical impedance spectroscopy and fitting according to the equivalent circuit, the Si P 、TiO2 / Si P and TiO2 / CN / Si P The Nyquist diagram of Figure 1 b and Table 1.
[0085] Table 1
[0086] <![CDATA[R s (Oh)]]> <![CDATA[R ct1 (Oh)]]> <![CDATA[R ct2 (Oh)]]> <![CDATA[TiO2 / CN / Si P ]]> 49 4557 <![CDATA[1.921×10 4 ]]> <![CDATA[TiO2 / Si P ]]> 109 <![CDATA[1.622×10 4 ]]> <![CDATA[2.046×10 4 ]]> <![CDATA[Si P ]]> 84 —— <![CDATA[1.045×10 6 ]]>
[0087] Among them, R ct1 , R ct2 and R s They represent the interfacial charge transfer resistance from Si to TiO2 inside the electrode, the charge transfer resistance from the electrode surface to the electrolyte, and the solution resistance. Obviously, R ct1 (TiO2 / CN / Si P ) is lower than R ct1 (TiO2 / Si P ), R ct1 (TiO2 / Si P ) is lower than R ct1 (Si P ), which further verifies the above explanation.
[0088] Compared with TiO2 / CN / Si P Electrode and TiO2 / CN / Si F The photocurrent intensity and reflectivity of the electrode, such as Figure 1 c shows TiO2 / CN / Si with microcone structure P The photocurrent intensity of the electrode is significantly higher than that of TiO2 / CN / Si without microcone structure. F This is because Si-based micro-pyramids are an excellent anti-reflection structure, so TiO2 / CN / Si P The reflectivity is lower than that of TiO2 / CN / Si F (like Figure 1 d), which increases the absorption of incident light and is beneficial to the improvement of photocurrent.
[0089] Example 2
[0090] On the basis of Example 1, the deposition time of PDA was adjusted, and the deposition time in step (5) was respectively placed at 30°C for 60, 80, 100, 120 and 140 minutes, and the other steps were the same as Example 1. TiO2 / CN / Si with different deposition times was obtained. P .
[0091] TiO2 / CN / Si P The photoelectric responsiveness of the electrode is crucial for MIP-PEC sensing. The loading of CN and TiO2 is closely related to the photocurrent density of the electrode. Figure 2 a shows that the CN loading can be increased with the increase of PDA deposition time, TiO2 / CN / Si P The photocurrent density of Si increases first and then decreases. This may be because with the increase of CN loading, the interfacial compatibility and conductivity between Si and TiO2 can be improved, which is beneficial to improving the photocurrent density of the electrode. However, due to excessive CN, Si P The distance of photogenerated carriers migrating outward will be extended, and the probability of electron and hole recombination will increase, which is not conducive to the improvement of electrode photocurrent density. Therefore, when the PDA deposition time is 100 minutes, TiO2 / CN / Si P The photocurrent density is the largest.
[0092] Example 3
[0093] On the basis of Example 1, the number of spin coating times of TiO2 sol was adjusted, and the spin coating in step (5) was performed 2, 4, 6, 8, and 10 times respectively, and the other steps were the same as Example 1. TiO2 / CN / Si with different spin coating times was obtained. P .
[0094] Figure 2 b shows that the TiO2 loading can be increased with the increase of TiO2 sol spin coating time, TiO2 / CN / Si P The photocurrent density increases first and then decreases. This may be because the heterojunction formed by Si and TiO2 can improve the separation efficiency of photogenerated carriers, which is beneficial to improve the photocurrent density of the photoelectrode. However, excessive loading of TiO2 will extend the outward migration distance of photogenerated carriers in the electrode, thereby increasing the probability of electron and hole recombination, which is not conducive to the improvement of the electrode photocurrent density. Therefore, when the number of spin coating is 4, TiO2 / CN / Si P The photocurrent density is the largest.
[0095] Example 4
[0096] (1) The TiO2 / CN / SiP obtained in Example 1 was immersed in a DA solution with a concentration of 2 mg / mL -1PBS solution (pH = 8.5) for 1 hour to pre-deposit PDA; then the above sample was placed in a solution containing functional monomer dopamine (2 mg mL -1 ) and template BSA (0.3 mg mL -1 ) in a PBS solution (pH = 8.5) and stirred and polymerized for 4 hours to obtain MIP / TiO2 / CN / Si P .
[0097] (2) MIP / TiO2 / CN / SiP was immersed in a mixture of 80 mL DCM and 0.8 mL TEA. Under N2 atmosphere, 20 mL DCM solution containing 2% BiBB was added dropwise to the above solution at 0°C for 1 hour, and then stirred at room temperature for 12 hours to obtain Br-MIP / TiO2 / CN / Si P ; Then, the BSA template was eluted with acetic acid / SDS (10% v / v: 5% w / v) for 90 min to form Br-rMIP / TiO2 / CN / Si P .
[0098] (3) The copper sheet was activated with an equal volume of 1 M hydrochloric acid and methanol mixed solution for 30 seconds and then fixed with a hollow rubber mold with a binder clip. Subsequently, the polymerization precursor solution (2 g PEGMA, 0.0374 g 2,2-bipyridine, 2 ml methanol and 4 ml H2O) was deoxygenated by N2 bubbling for 30 min and added to the hollow part of the rubber mold. The initiator-functionalized Br-rMIP / TiO2 / CN / SiP was covered on the top of the rubber mold to ensure contact with the polymerization precursor solution. After polymerization at room temperature for 2 hours, rMIP(PB) / TiO2 / CN / Si P .
[0099] Comparative Example 3
[0100] The TiO2 / CN / SiP obtained in Example 1 was immersed in DA with a concentration of 2 mg / mL -1 The electrode was prepared by pre-deposition of polydopamine in a PBS solution (pH = 8.5) for 1 hour, and the polymerization reaction was carried out under stirring for 4 hours to obtain an electrode without a template material, which was labeled as NIP / TiO2 / CN / Si P .
[0101] Comparative Example 4
[0102] The TiO2 / CN / SiP obtained in Example 1 was immersed in DA with a concentration of 2 mg / mL -1 PBS solution (pH = 8.5) for 1 hour to pre-deposit PDA; then the above sample was placed in a solution containing functional monomer dopamine (2 mg / mL -1 ) and template BSA (0.3 mg mL-1 ) in a PBS solution (pH = 8.5) and stirred and polymerized for 4 hours to obtain MIP / TiO2 / CN / Si P Then, the BSA template was eluted with acetic acid / SDS (10% v / v: 5% w / v) for 90 min to obtain the electrode rMIP / TiO2 / CN / Si without polymer brush. P .
[0103] rMIP(PB) / TiO2 / CN / Si P The schematic diagram of the electrode production process is as follows Figure 3 shown.
[0104] According to the characteristics of anisotropic etching of
[100] type single crystal silicon in alkaline solution, a micro-pyramid structure is constructed on the Si surface to obtain Si P , which has the effect of reducing the reflection of incident light and increasing absorption, thereby improving the intensity of the photoelectric signal of the MIP-PEC electrode.
[0105] By doping Si P The formation of a buried pn junction on the surface is beneficial to improving the separation efficiency of photogenerated carriers. Figure 4 As shown in a, the average width and tilt angle of Si pyramids are 5 μm and 54.7°, respectively. Figure 5 As shown, the obtained rMIP(PB) / TiO2 / CN / Si P SEM and corresponding element mapping images show that phosphorus is evenly distributed in Si P surface.
[0106] Nitrogen-doped carbon (CN) layers were induced on Si by calcining PDA P Surface aggregation to obtain CN / Si P , which is beneficial to Si P The photogenerated carriers migrate outward. Figure 4 As shown in b, CN is densely distributed on Si in the form of nanoparticles. P surface.
[0107] TiO2 assembled on CN / Si by spin coating and annealing P Surface, TiO2 / CN / Si P , it can be used with Si P Form a heterojunction and improve TiO2 / CN / Si P The overall photogenerated carrier separation efficiency of the electrode is improved, thereby increasing the intensity of the photoelectric signal. Figure 4 As shown in c, TiO2 particles are evenly distributed on CN / Si P surface. Figure 4 d It can be seen that the crystal types of TiO2 are anatase and rutile.
[0108] like Figure 4 As shown in e, the rough MIP layer (MIP / TiO2 / CN / Si P ) is the reaction of dopamine on TiO2 / CN / Si in the presence of BSA template. P Surface self-polymerization. Figure 4 NIP / TiO2 / CN / Si in f P In contrast, large PDA particles on the MIP layer are less likely to occur because the interaction between the BSA template and dopamine inhibits the generation of particle aggregation. Figure 4 Curves a and b in h are the FTIR spectra of PDA and BSA imprinted PDA, respectively. Compared with curve a, a peak at 1656 cm appears on curve b. -1 The new peak belongs to the stretching vibration peak of C=O bond in BSA, which further proves the successful preparation of MIP layer.
[0109] Without removing the template (Br-MIP / TiO2 / CN / Si P ), the amino groups on the MIP layer reacted with the acyl bromide in BIBB, introducing the functional group C-Br with the ability to initiate ATRP, and its corresponding characteristic peak appeared at 685 cm in the FTIR spectrum. -1 Where Figure 4 h is shown in curve c.
[0110] After the BSA template was removed, C-Br was retained in the non-imprinted part of the MIP layer, resulting in the Cu(0)-mediated SI-ATRP reaction of PEGMA in the non-imprinted part of the MIP layer to form a polymer brush (rMIP(PB) / TiO2 / CN / Si P PEGMA was chosen as the modified polymer brush after imprinting due to the protein repulsion effect of the PEG segment, which is attributed to the low interfacial free energy of the PEG-water interface and the absence of hydrogen bonding and electrostatic interactions with proteins. It can reduce the nonspecific adsorption of proteins to non-imprinted sites of the MIP. Figure 4 g shows that the electrode surface becomes smooth after modification with polymer brushes on the MIP layer. In addition, the corresponding FTIR spectra show Figure 4 In the curve d of h, 2870cm -1 The peak at 1726 cm is assigned to the stretching vibration of the CH bond in alkanes. -1 and 1245cm -1 The peaks at 1452 cm are related to the characteristic peaks of the C=O bond in aliphatic and the COC bond in ether. -1 and 1106cm -1The enhanced peaks correspond to the CH2 deformation vibration in the alkane and the introduction of the terminal hydroxyl CO bond, respectively, which proves the successful synthesis of the polymer brush.
[0111] Example 5
[0112] On the basis of Example 4, the imprinting conditions were optimized and the imprinting time in step (1) was adjusted to 2, 3, 4, 5 and 6 hours respectively. The other conditions and steps were the same as those in Example 4.
[0113] The change of photocurrent density (ΔI) before and after elution of template BSA. Figure 6 a shows the effect of imprinting time on MIP / TiO2 / CN / Si P The influence of ΔI. Figure 6 In a, as the imprinting time increases, ΔI increases first and then decreases, reaching the maximum value when the imprinting time is 4 hours. This is because the imprinting time is related to the thickness of the MIP layer. Too short an imprinting time will cause the MIP layer to become thinner and reduce the number of imprinting points, which is not conducive to the sensing sensitivity of the electrode. Too long an imprinting time will cause the MIP layer to become thicker, making it difficult to elute the template BSA inside, reducing the sensing sensitivity of the electrode.
[0114] Example 6
[0115] Based on Example 4, the imprinting conditions were optimized and the template BSA concentrations in step (1) were adjusted to 0.1, 0.2, 0.3, 0.4, and 0.5 mg / mL, respectively. -1 , other conditions and steps are the same as those in Example 4.
[0116] The change of photocurrent density (ΔI) before and after elution of template BSA. Figure 6 b shows the effect of template BSA concentration on MIP / TiO2 / CN / Si P With the increase of template BSA concentration, ΔI also showed a trend of increasing first and then decreasing. When the BSA concentration was 0.3 mg 〃 mL -1 This is because fewer imprinting sites are formed at low BSA concentrations, which is detrimental to the sensing sensitivity of the electrode. Too high BSA concentrations can cause self-aggregation, which then reduces the imprinting sites and thus reduces the sensing sensitivity of the electrode.
[0117] Example 7
[0118] On the basis of Example 4, the imprinting conditions were optimized and the template elution time in step (2) was adjusted to 30, 60, 90 and 120 min respectively. The other conditions and steps were the same as those in Example 4.
[0119] The change of photocurrent density (ΔI) before and after elution of template BSA. Figure 6 c shows the effect of template elution time on MIP / TiO2 / CN / Si P The ΔI value increased with the extension of template elution time, and then stabilized after the elution time reached 90 minutes, indicating that the template had been completely removed at this time.
[0120] Example 8
[0121] On the basis of Example 4, the modification time of the polymer brush was optimized, and the polymerization time in step (3) was adjusted to 0, 30, 60, 90, 120, 150, and 180 min, respectively. The other conditions and steps were the same as those in Example 4.
[0122] rMIP(PB) / TiO2 / CN / Si under different polymer brush modification time P The photocurrent density is Figure 7 As shown in (a), when the polymer brush modification time reaches 120 min, the photocurrent density remains unchanged, indicating that the polymerization reaction has been completed.
[0123] Example 9
[0124] The rMIP(PB) / TiO2 / CN / Si prepared in Example 4 P Applied to BSA detection. Photoelectrochemical tests were performed in an electrochemical workstation, using a xenon lamp as the excitation light source and the incident light power was maintained at 100 mW 〃 cm -2 .
[0125] Prepare a 0.1M Tris-HCl buffer solution with a pH of 7.4, which contains 0.1M sodium chloride and 0.05M potassium chloride, and use this to prepare a concentration of 10 -13 mg〃mL -1 The measurement was performed using a three-electrode system. The rMIP(PB) / TiO2 / CN / Si prepared in Example 4 P The working electrode was immersed in the prepared BSA solution, the Ag / AgCl electrode was used as the reference electrode, and the platinum mesh was used as the counter electrode. The electrochemical tests were carried out under a bias voltage of -0.264Vvs Ag / AgCl, and the electrochemical impedance spectroscopy was tested in the frequency range of 0.1Hz to 100kHz. The ambient temperature was stabilized at 25℃. All measurements were calibrated to E NHE =E Ag / AgCl +0.197, -0.264V vs Ag / AgCl is equivalent to -0.067V vs NHE, which is the reduction potential of dissolved oxygen.
[0126] The time for the working electrode to be immersed in the BSA solution was optimized and the adjusted times were 2, 4, 6, 8, 10, 12, and 14 min, respectively.
[0127] When rMIP(PB) / TiO2 / CN / Si P When the incubation time for BSA reached 10 minutes, ΔI reached its maximum value and then changed little, such as Figure 7 Therefore, the optimal incubation time for BSA in this system is 10 minutes, which is also the fixed incubation time in the subsequent analysis and detection process.
[0128] On this basis, different concentrations of BSA solutions were prepared, and the photocurrent density and linear analysis were as follows: Figure 8 a and 8b, ΔI and the logarithm of BSA concentration (logC BSA ) in 10 -16 Up to 10 -9 mg〃mL -1 There is a linear relationship within the range. The linear regression equation is ΔI = 0.07396lgC BSA +1.4716(Linear correlation coefficient R 2 =0.993). The detection limit (LOD) was 2.203×10 -17 mg〃mL -1 (S / N=3). This indicates that rMIP(PB) / TiO2 / CN / Si P It has good quantitative analysis capability for BSA.
[0129] The definition and detailed calculation method of the imprinting factor refer to the literature (Chen, L., Wang, X., Lu, W., Wu, X., Li, J., 2016. Chem. Soc. Rev. 45, 2137-2211.), and the value of the imprinting factor (IF) is calculated by the following formula:
[0130] IF=ΔI MIP / ΔI NIP
[0131] In the formula, ΔI MIP and ΔI NIP They represent the changes in photocurrent density when the electrode has the maximum response concentration when there is a MIP layer and a NIP layer. Fig. 9 a It can be seen that rMIP(PB) / TiO2 / CN / Si P The IF value of the electrode is 10 -9 mg〃mL -1 ΔI MIP1 With BSA concentration of 10 -13 mg〃mL -1 ΔI NIP The ratio of Fig. 9 b It can be seen that rMIP / TiO2 / CN / Si P The IF value of the electrode is 10-9 mg〃mL -1 ΔI MIP2 With BSA concentration of 10 -13 mg〃mL -1 ΔI NIP ratio.
[0132] The results are as follows Fig. 9 It shows that rMIP(PB) / TiO2 / CN / Si P The imprint factor (IF = 7.06) is higher than that of rMIP / TiO2 / CN / Si in Comparative Example 4. P (IF = 5.10), which further proves that rMIP (PB) / TiO2 / CN / Si P It has stronger selectivity for BSA.
[0133] Example 10
[0134] In order to evaluate the rMIP(PB) / TiO2 / CN / Si P To improve the qualitative analysis ability of BSA, functional group interferents similar to BSA were introduced into the detection system, including BHb, L-Tryptophan, Glycine, L-Leucine, L-Phenylalanine, Glutathione, such as Fig.10 a. The concentration of the interfering substance is 100 times that of BSA (10 -11 mg〃mL -1 ). Here, R% = ΔI / ΔI BSA × 100%, where ΔI is the change in photocurrent density caused by various interferents, ΔI BSA The photocurrent density change caused by BSA, the specific detection ability of the electrode is evaluated by R%. The test results are as follows Fig.10 As shown in b, it can be seen that under the same test conditions, rMIP(PB) / TiO2 / CN / Si P The R% of all interfering substances is much lower than that of BSA. Especially in the mixed solution of low concentration BSA and high concentration interfering substances, rMIP(PB) / TiO2 / CN / Si P The R% for BSA is 99.09%, which is much better than rMIP / TiO2 / CN / Si P , indicating that it has good qualitative analysis ability for BSA. The reasons are as follows. On the one hand, BSA molecules can preferentially occupy the imprinting sites with interferents. On the other hand, the polymer brush can avoid the adsorption of interferents at non-imprinting sites.
[0135] Embodiment 11
[0136] Repeatability and stability are also important factors in evaluating rMIP(PB) / TiO2 / CN / Si P In this Example 11, five rMIP (PB) / TiO2 / CN / Si were prepared under the same conditions. P The initial photocurrent density corresponding to the electrode is as follows: Fig.11 As shown in a, the relative standard deviation (RSD) is 1.5%, indicating that the electrode exhibits good repeatability. Then, one of the above electrodes is randomly selected, and its photoelectric signal in the optical switching cycle within 400 seconds is shown in Fig.11 b. The corresponding RSD is 2.6%, indicating that rMIP(PB) / TiO2 / CN / Si P Has good stability.
[0137] Example 12
[0138] rMIP(PB) / TiO2 / CN / Si P The electrode is used to detect BAS in milk. Specifically, a 0.1M Tris-HCl buffer solution with a pH of 7.4 is prepared, which contains 0.1M sodium chloride and 0.05M potassium chloride. The Tris-HCl buffer solution is mixed with milk in a volume ratio of 9:1 to form a mixed solution. The mixed solution is then used to prepare a 10% concentration of -13 , 10 -11 , 10 -9 mg〃mL -1 The other steps are the same as those in Example 9. The test results are shown in Table 2.
[0139] Table 2
[0140] <![CDATA[Concentration of BSA solution (mg〃mL -1 )]]> <![CDATA[Detection concentration (mg〃mL -1 )]]> R(%) RSD(%) <![CDATA[10 -13 ]]> <![CDATA[9.099×10 -14 ]]> 91.0 4.31 <![CDATA[10 -11 ]]> <![CDATA[1.064×10 -11 ]]> 106.4 6.12 <![CDATA[10 -9 ]]> <![CDATA[9.121×10 -10 ]]> 91.2 3.56
[0141] It can be seen from Table 2 that under the same test conditions, no matter what the BSA solution concentration is, rMIP(PB) / TiO2 / CN / Si P The R% of BSA was greater than 91.0%, indicating that even in milk, rMIP(PB) / TiO2 / CN / Si P The good qualitative analysis ability for BSA further proves the practical value of the method of the present invention.
[0142] Embodiment 13
[0143] In this example, based on Example 4, BSA was replaced with acetylcholine (Ach), and the other steps were the same as those in Example 4. The method of the present invention was applied to the detection of acetylcholine (Ach) to prove its universal applicability. The electrode finally obtained was named rMIP(PB) / TiO2 / CN / Si P-Ach. Ach is a neurotransmitter that can irritate the skin and cause allergic reactions. It is a banned ingredient in cosmetics and was therefore used as a model substance for another analysis.
[0144] Based on ACh as a template, the electrode with polymer brush (refer to Example 4) and the electrode without polymer brush (refer to Comparative Example 4) were named rMIP(PB) / TiO2 / CN / Si P -Ach and rMIP / TiO2 / CN / Si P -Ach. Fig.12 a and 12b, at 10 -8 to 10 -4 M, ΔI and the logarithm of Ach concentration (logC Ach ) is linearly related, and the calibration equation is ΔI=0.0443lgC Ach +0.719(R 2 =0.993) and LOD was 0.346 nM, indicating that the method of modifying polymer brushes has general applicability to other analytes.
[0145] At the same time, under the above detection conditions, rMIP(PB) / TiO2 / CN / Si P -Ach and rMIP / TiO2 / CN / Si P -Ach's specific recognition ability for Ach. Fig.12 c and 12d show that in the process of detecting ACh, rMIP(PB) / TiO2 / CN / Si P R MIP / TiO2 / CN / Si P Better anti-interference ability.
[0146] In addition, if Fig.12 As shown in e, under the same preparation conditions, five rMIP(PB) / TiO2 / CN / Si P -Ach electrode is very close. The corresponding RSD is 2.6%, showing that rMIP(PB) / TiO2 / CN / Si P -Good repeatability of Ach. Fig.12 f shows rMIP(PB) / TiO2 / CN / Si P -Ach photocurrent signal during the 400 s photo-switching cycle. The photocurrent response was similar during and after 20 on / off irradiation cycles, indicating that rMIP(PB) / TiO2 / CN / Si P -Ach had good stability with an RSD of 0.3%.
[0147] The present invention provides a molecular imprinting photoelectrochemical (MIP-PEC) sensor based on polydopamine (PDA) monomer. However, the abundant active functional groups on the surface of PDA lead to non-specific adsorption at non-imprinting sites, resulting in a decrease in the ability of the MIP-PEC sensor to qualitatively analyze proteins. In the present invention, a photoinduced silicon electrode is sequentially buried with nodes, nitrogen-doped carbon and TiO2 (TiO2 / CN / Si P ) modification is beneficial to amplify its photoelectric signal and improve its detection sensitivity. P A MIP layer based on dopamine functional monomers and bovine serum albumin (BSA) template was fabricated on the electrode to specifically recognize BSA. In addition, the non-imprinting sites of the MIP layer were blocked by introducing a polymer brush, which can reduce the probability of nonspecific adsorption. The experimental results show that as the imprinting factor increases from 5.10 to 7.06, the specific recognition ability of the MIP-PEC sensor for BSA is significantly improved. At the same time, the sensor signal is closely related to the BSA concentration at 10 -16 ~10 -9 mg〃mL -1 The detection limit was 2.203×10 -17 mg〃mL -1 (S / N=3). In addition, it was also successfully analyzed by using the template of acetylcholine, which confirmed the universality of the proposed method.
[0148] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A polymer brush modified molecular imprinting photoelectrochemical sensor, characterized in that: include, an electrode substrate, comprising a semiconductor material capable of generating electrons and holes under illumination; A molecular imprinting layer is attached to the surface of the electrode substrate, wherein the molecular imprinting layer has a plurality of template sites, each template site being specific to one or more of bovine serum albumin, insulin, bovine hemoglobin, horse myoglobin, human growth hormone, ribonuclease, glucose oxidase, catalase, and a raw material compound prohibited by cosmetics; and, a polymer brush, the polymer brush occupying a non-template site portion of the molecular imprinting layer; Wherein, the material of the polymer brush is selected from one of PEGMA and its derivatives.
2. The polymer brush modified molecular imprinting photoelectrochemical sensor according to claim 1, characterized in that: The material of the molecular imprinting layer is selected from one or more of polydopamine, polyacrylamide and its derivatives, polyacrylic acid and its derivatives, chitosan, gelatin, polyvinyl alcohol, polymethacrylic acid, silicon dioxide, and titanium dioxide.
3. The polymer brush modified molecular imprinting photoelectrochemical sensor according to claim 1, characterized in that: The electrode substrate comprises a silicon substrate, a carbon layer or a doped carbon layer attached to the silicon substrate, and a semiconductor material layer attached to the carbon layer or the doped carbon layer; Wherein, the silicon substrate has a micro-pyramid structure surface.
4. The method for preparing a polymer brush modified molecular imprinting photoelectrochemical sensor according to any one of claims 1 to 3, characterized in that: include, providing an electrode substrate; A molecular imprinting layer is formed by polymerizing a molecular imprinting layer monomer containing a template material on the surface of an electrode substrate; The eluted template material forms a plurality of template sites on the molecular imprinting layer and a functional group capable of initiating atom transfer radical polymerization is formed on the non-template site portion; The polymer brushes are formed by functional group-mediated atom transfer radical polymerization of the polymer precursor at the non-template site.
5. The method for preparing the polymer brush modified molecular imprinting photoelectrochemical sensor according to claim 4, characterized in that: The molecular imprinting layer monomer containing the template material is polymerized on the surface of the electrode substrate, and the electrode substrate is placed in a PBS solution containing the molecular imprinting layer monomer and the template material, and the polymerization is stirred to obtain the electrode substrate with the molecular imprinting layer.
6. The method for preparing the polymer brush modified molecular imprinting photoelectrochemical sensor according to claim 4, characterized in that: The template material is eluted by immersing the electrode substrate with the molecular imprinting layer in a mixture of dichloromethane and triethylamine, and under a N2 atmosphere, a dichloromethane solution containing 2-bromoisobutyryl bromide is added dropwise to the above solution, and then stirred at room temperature, and then the template material is eluted with acetic acid / sodium dodecyl sulfate to form an electrode substrate with a molecular imprinting layer having template sites and functional groups.
7. The method for preparing a polymer brush modified molecular imprinting photoelectrochemical sensor according to claim 6, characterized in that: The method comprises the following steps: atom transfer radical polymerization of a polymer precursor at a non-template site is mediated by a functional group, the polymer precursor solution is deoxygenated by N2 bubbling, an electrode substrate having a molecular imprinting layer with template sites and functional groups is contacted with the polymer precursor solution, and polymerization is performed at room temperature to obtain a polymer brush modified molecular imprinting photoelectrochemical sensor.
8. The method for preparing a polymer brush modified molecular imprinting photoelectrochemical sensor according to claim 4, characterized in that: The specific method of providing the electrode substrate includes: The silicon wafer is etched in an alkaline solution to form a silicon wafer having a micro-pyramid structure surface; Putting the silicon wafer into a polymer monomer solution for polymerization, and polymerizing to form a polymer layer on the surface of the silicon wafer; calcining the polymer layer to carbonize the polymer layer and form a carbon layer or a doped carbon layer on the silicon wafer; The semiconductor material is assembled on the carbon layer or the doped carbon layer, and the electrode substrate is obtained after calcination.
9. Use of the polymer brush modified molecular imprinting photoelectrochemical sensor according to any one of claims 1 to 3 in the detection of biomolecules and / or cosmetics.
Citation Information
Patent Citations
Surface plasma resonance sensor chip and preparation method thereof
CN101887017A
Preparation method for molecularly imprinted microsphere surface grafted hydrophilic polymer brush
CN103509158A